THE EFFECT OF EDUCATIONAL TRAINING, ORGANIZATIONAL SUPPORT, EMOTIONAL INTELLIGENCE AND WORK FACILITIES ON EMPLOYEE PERFORMANCE - Prabowo, Adelia Maritza Prabowo; Kusumastuti, Yuni (Jurnal Ecoment Global, 2025)
Abstract Objective: This study aims to determine the effect of Education Training, Organizational Support, Emotional Intelligence and Work Facilities on Employee Performance at the Meteorology, Climatology and Geophysics Agency Region II. Design/Methods/Approach: The research method used is quantitative descriptive. The data analysis technique employed in this study is multiple linear regression. The sampling method used in this research is saturation sampling, with a total sample size of 80 employees. Data were collected through a questionnaire using a Likert scale, which was processed using Microsoft Excel 19 and Statistics Product Service and Solution (SPSS) version 26 software. Findings: The results of this study indicate that the variables of Education Training and Emotional Intelligence have a positive and significant effect on Employee Performance, while the variables of Organizational Support and Work Facilities have a positive and insignificant effect on Employee Performance. Originality/Value: The novelty of this study lies in the results that are different from previous studies, thus proving that the results of the research presented by previous researchers are inconsistent. Practical/Policy implication: The results of this study are expected to contribute to the development of human resource management strategies at BBMKG Region II Tangerang Selatan. Keywords: Education Training, Organizational Support, Emotional Intelligence, Work Facilities, Employee Performance